2012
DOI: 10.1177/0748233712440140
|View full text |Cite
|
Sign up to set email alerts
|

The genotoxic, hepatotoxic, nephrotoxic, haematotoxic and histopathological effects in rats after aluminium chronic intoxication

Abstract: Aluminium (Al) is used in water purification and is also present in several manufactured foods and medicines. Al is known to induce a broad range of physiological, biochemical and behavioural dysfunctions in laboratory animals and humans. This investigation was carried out to investigate the effects of subchronic exposure to Al (as AlCl3) in rats. Sprague-Dawley rats were randomly separated into two groups. Group 1 rats treated with sodium chloride served as the control, group 2 rats were treated with Al (as A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 61 publications
7
37
0
2
Order By: Relevance
“…Geyikoĝlu et al (2013) conducted a liver MN assay in adult male Sprague-Dawley rats given daily ip injections of AlCl 3 at 5 mg/kg-day for 10 weeks. A control group of six rats received daily ip injections of saline.…”
Section: Immunology and Vaccine Adjuvantsmentioning
confidence: 99%
“…Geyikoĝlu et al (2013) conducted a liver MN assay in adult male Sprague-Dawley rats given daily ip injections of AlCl 3 at 5 mg/kg-day for 10 weeks. A control group of six rats received daily ip injections of saline.…”
Section: Immunology and Vaccine Adjuvantsmentioning
confidence: 99%
“…Numerous studies have suggested that hesperidin shows its neuroprotective action in cerebral ischemia reperfusion injury, hypoxia-ischemic brain injury, Huntington disease, cisplatin-induced neurotoxicity, stroke, pentylenetetrazole (PTZ)-induced kindling, and associated cognitive dysfunction [20][21][22][23][24]. On the other hand, [1,4] dioxin-6-yl] chroman-4-one] is a polyphenolic flavonoid and the chief component of silymarin derived from the herb milk thistle (Silybum marianum). It has been reported to have potent antioxidant and antiinflammatory properties [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately, 7600 μg/day aluminum is consumed by human through different routes like food, drinking water, soil, and dust ingestion [1]. Several experimental studies show that aluminum compounds are associated with a wide range of pathological conditions such as Alzheimer's disease, reproductive toxicity, cytoskeletal pathologies, microcytic anemia, osteomalacia, dialysis encephalopathy, and hepato-renotoxicity [2][3][4][5]. Prolonged exposure to aluminum is most prominently associated with neurotoxic events [6].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the main known toxicological effects of aluminium included anaemia (7)(8)(9), neurodegenerative disorders such as Alzheimer disease and dementia (10)(11)(12)(13)(14)(15)(16)(17), amyotrophic lateral sclerosis (18)(19)(20), hepatotoxicity (21)(22)(23), or diverse reproductive disorders (24)(25)(26)(27)(28)(29)(30). The toxic effects associated with aluminium are due, in most situations, to generation of reactive oxygen species (ROS) (31,32), conducing to cellular lipidic proteinic and/or DNA oxidative deterioration (33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%